آراء مصطفى لطفي المنفلوطي في السياسة (دراسة تحليلية على مقال "السياسة" في النظرات): Pemikiran, Mushtafa Luthfi Al-Manfaluthi dalam Politik - Cut Keumalawati (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2020)
Almost every day we often hear the term political. Where the print and electronic media filled with political news, especially when the election ahead. The political term is usually associated with black and dirty deeds. Mushtafa Luthfi Al-Manfaluthi, a great Egyptian writer whose works have raised many social issues such as ignorance, misery, pain, and moral dedication. One of his writings on pain and misery is a political issue. Therefore, this study was made to see the truth and suitability of expression anger Mushtafa Luthfi Al-Manfaluthi about the cruel politicians in power. In this study, the author finds the many conformities of the expression of Mushtafa Luthfi about the politician's ruthlessness in power, various ways will be taken by them to seize power. This study concludes that politicians are like sycophants in which they justify many ways to become rulers without thinking of the fate of their people.